Accumulation of worn-out GBM material substantially contributes to mesangial matrix expansion in diabetic nephropathy - Kriz, Wilhelm; Federico, Giuseppina; Gröne, Elisabeth; Gröne, Hermann-Josef (American journal of physiology. Renal physiology, 2017)
Thickening of the glomerular basement membrane (GBM) and expansion of the mesangial matrix are hallmarks of diabetic nephropathy (DN), generally considered to emerge from different sites of overproduction: GBM components from podocytes and mesangial matrix from mesangial cells. Reevaluation of 918 biopsies with DN revealed strong evidence that these mechanisms are connected to each other, wherein excess GBM components fail to undergo degradation and are deposited in the mesangium. These data do not exclude that mesangial cells also synthesize components that contribute to the accumulation of matrix in the mesangium. Light, electron microscopic, immunofluorescence, and in situ hybridization studies clearly show that the thickening of the GBM is due not only to overproduction of components of the mature GBM (α3 and α5 chains of collagen IV and agrin) by podocytes but also to resumed increased synthesis of the α1 chain of collagen IV and of perlecan by endothelial cells usually seen during embryonic development. We hypothesize that these abnormal production mechanisms are caused by different processes: overproduction of mature GBM-components by the diabetic milieu and regression of endothelial cells to an embryonic production mode by decreased availability of mediators from podocytes.
Gesehen am 12.07.2018